Effect of parameters on local stress field in single-lap bolted joints with the interference fit. (3rd May 2016) - Jiang, Jiefeng; Bi, Yunbo
From the interference fit bolt installation to tensile loading stage in single-lap joint with a hi-lock bolt, the stress and strain fields were studied experimentally and numerically. A three-dimensional finite element model was generated to simulate the experimental setup, which was validated using the experimental data. The fatigue behavior of the bolted joint is influenced by the local stress fields on the faying surface near the holes in single-lap joints. Therefore, with the aim to improve design awareness, the effects of the parameters on the local stress fields were investigated by means of finite element simulation. With an increase in the interference fit size, the occurred position of the maximum stress values on the upper plate faying surface moves away from the hole edge gradually. As the clamping force or friction coefficient increases, the position of larger stress area is changed to the side of bearing load from the transverse direction. The lap geometry of the bolted joint as well as the amplitude of tensile load has apparent impact on the maximum stress value.